Analisis Komparatif Pendapatan Usahatani Kelapa Sawit Kelompok Iga Dan Plasma Di Desa Gunungsari Kecamatan Pasangkayu Kabupaten Mamuju Utara - Mustapa, I Wayan (AGROTEKBIS, 2013)
The aim of the study was (i) to analyse the income of oil palm farm of the Iga and Plasma groups, and (ii) to analyse the comparation of the income of oil palm farm of the both of groups. The respondents were farmers of oil palm of the both of groups. The respondents were taken by technique of unproportionally stratified random sampling. There are 130 population of the farmer of oil palm whom consist of 60 farmers of the Iga group, and 70 of the Plasma group. For every group was taken 15 respondents as sample. Methods of analyses used were the analyses of income, and the analyses of comparation. Analysis results showed that the average income of Iga group of oil palm farmers was greater than plasma group, i.e. IRD 2.13 million per ha vs IRD 1.71 million per ha. Thus, there was sifnificantly difference between the income of Iga group and Plasma group. It was indicated by t-hit > t-tab(?=1%; df=29), i.e. 19.356 vs 2.763. It means that Ho is rejected, and H1 is verified that there was sifnificantly difference between the income of the both groups that the income of Iga group of oil palm farmers was greater than plasma group